2006
DOI: 10.7589/0090-3558-42.2.290
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Survey for Brucella Spp., Phocid Herpesvirus-1, Phocid Herpesvirus-2, and Phocine Distemper Virus in Harbor Seals From Alaska, 1976–1999

Abstract: ABSTRACT:Harbor seals (Phoca vitulina richardsi) were captured in the coastal regions of Southeast Alaska, Gulf of Alaska, Prince William Sound (PWS), and Kodiak Island during 1976-1999. Blood was collected from 286 seals. Sera were tested for evidence of exposure to Brucella spp., phocid herpesvirus-1 (PhoHV-1), phocid herpesvirus-2 (PhHV-2), and phocine distemper virus (PDV). Antibody prevalence rates were 46% (46/100) for Brucella spp., 93% (225/243) for PhoHV-1, 0% (0/286) for PhHV-2, and 1% (2/160) for PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 52 publications
2
29
0
1
Order By: Relevance
“…Fourteen preweaned, live pups sampled from the same population one year later were all negative, but 3 of 61 adult females were antibody-positive (Blank et al, 2001). In harbor seals (Phoca vitulina), 2 of 18 pups (undefined weaning status) were positive to Brucella on iELISA and cELISA and higher prevalences were found in both juvenile and adult age classes (Zarnke et al, 2006). Increased prevalence with age was also noted in Hawaiian monk seals, in which progressively higher proportions of animals with Brucella antibodies were found in the weaned pup, juvenile, and adult age classes (Aguirre et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…Fourteen preweaned, live pups sampled from the same population one year later were all negative, but 3 of 61 adult females were antibody-positive (Blank et al, 2001). In harbor seals (Phoca vitulina), 2 of 18 pups (undefined weaning status) were positive to Brucella on iELISA and cELISA and higher prevalences were found in both juvenile and adult age classes (Zarnke et al, 2006). Increased prevalence with age was also noted in Hawaiian monk seals, in which progressively higher proportions of animals with Brucella antibodies were found in the weaned pup, juvenile, and adult age classes (Aguirre et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…Prevalence increased with age, as has been reported for Brucella spp. exposure in other marine mammals (Zarnke et al, 2006). That increase may be associated with increased sexual activity with maturation.…”
Section: Discussionmentioning
confidence: 96%
“…Reidarson et al (1998) detected titers to dolphin morbillivirus in 6 of 18 common dolphins Delphinis delphis stranded in southern California, but characteristic morbilliviral lesions were not observed. Duignan et al (1995) found no serologic evidence of morbillivirus in 80 harbor seals from the Pacific coast of North America, nor did Zarnke et al (2006) in 286 harbor seals from Alaska. Recently, however, viral nucleic acid identical to an isolate from the 2002 PDV outbreak in the North Sea was reported in sea otters in Alaska (Goldstein et al 2009).…”
Section: Morbillivirusmentioning
confidence: 99%
“…Surveys of apparently healthy seals in remote areas considered to be relatively pristine have demonstrated exposure to zoonotic bacteria such as Brucella spp., and protozoa such as Giardia, T. gondii, and Sarcocystis neurona (Olson et al 1997, Dubey et al 2003, Zarnke et al 2006, Jensen et al 2010, highlighting the role that marine mammals may play both as sentinels of pathogen pollution in the marine environment and as potential reservoirs for pathogens that could affect humans (Ross 2000). There are thus a variety of zoonotic organisms in the marine environment that can impact both marine mammal and human health.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%